The Economic Contributions of Agricultural Tourism in Michigan. Issue 3 (1st July 2016) - Veeck, Gregory; Hallett, Lucius; Che, Deborah; Veeck, Ann
Abstract : Family farms have long generated income from agricultural tourism including U‐picks, wagon rides, corn mazes and petting zoos, but contemporary agricultural tourism reflects much greater sophistication in terms of product variety, services, activities, and marketing. In Michigan, farm operators have moved beyond classic products and activities and the traditional consumer base. New sources of revenue derive from classes on beer, cider, mead and wine making, yarn spinning, perfume/soap‐making, farm markets, fishing, educational classes, school tours and hospitality including weddings and on‐farm restaurants. This case study of Michigan agricultural tourism reports results from a systematic survey of 154 agritourism operations conducted throughout the state during summer and fall of 2013 with a focus on the economic benefits of the fast‐changing sector. This study summarizes tax revenues, sales and employment trends for the farm operations participating in the survey but also quantitatively assesses the contribution of agricultural tourism to Michigan's economy through an extrapolation of the sample to estimate state‐wide totals. Results from multivariate regression analysis intended to identify relationships between employment, advertising and scale to gross sales per day are also reported. These analyses show the importance of agricultural tourism to rural and peri‐urban places in Michigan and throughout the nation, while raising concerns about a growing division between large and small operators and what this growing gap may mean for the future of the sector.